\(\sqrt{31-12\sqrt{3}}-\sqrt{31+12\sqrt{3}}\)

tính

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 7 2021

\(\sqrt{31-12\sqrt{3}}-\sqrt{31+12\sqrt{3}}\)

\(=\sqrt{\left(3\sqrt{3}\right)^2-2.3\sqrt{3}.2+2^2}-\sqrt{\left(3\sqrt{3}\right)^2+2.3\sqrt{3}.2+2^2}\)

\(=\sqrt{\left(3\sqrt{3}-2\right)^2}-\sqrt{\left(3\sqrt{3}+2\right)^2}=\left|3\sqrt{3}-2\right|-\left|3\sqrt{3}+2\right|\)

\(=3\sqrt{3}-2-3\sqrt{3}-2=-4\)

30 tháng 7 2021

a yêu e

Bài 1 : \(\sqrt{49-12\sqrt{5}}+\sqrt{49+12\sqrt{5}}\)

\(=\sqrt{45-4\sqrt{45}+4}+\sqrt{45+4\sqrt{45}+4}\)

\(=\sqrt{\left(\sqrt{45}-2\right)^2}+\sqrt{\left(\sqrt{45}+2\right)^2}\)

\(=\sqrt{45}-2+\sqrt{45}+2=2\sqrt{45}\)

Bài 2 : \(\sqrt{29+12\sqrt{5}}+\sqrt{29-12\sqrt{5}}\)

\(=\sqrt{20+6\sqrt{20}+9}+\sqrt{20-6\sqrt{20}+9}\)

\(=\sqrt{\left(\sqrt{20}+3\right)^2}+\sqrt{\left(\sqrt{20}-3\right)^2}\)

\(=\sqrt{20}+3+\sqrt{20}-3=2\sqrt{20}\)

Bài 3 : \(\sqrt{31-12\sqrt{3}}+\sqrt{31+12\sqrt{3}}\)

\(=\sqrt{27-4\sqrt{27}+4}+\sqrt{27+4\sqrt{27}+4}\)

\(=\sqrt{\left(\sqrt{27}-2\right)^2}+\sqrt{\left(\sqrt{27}+2\right)^2}\)

\(=\sqrt{27}-2+\sqrt{27}+2=2\sqrt{27}\)

Chúc bạn học tốt

1 tháng 8 2018

4 , Ta có :

\(\sqrt{39-12\sqrt{3}}-\sqrt{39+12\sqrt{3}}\)

\(=\sqrt{3-2.6.\sqrt{3}+6^2}-\sqrt{3+2.6.\sqrt{3}+6^2}\)

\(=\sqrt{\left(\sqrt{3}-6\right)^2}-\sqrt{\left(\sqrt{3}+6\right)^2}\)

\(=\left|\sqrt{3}-6\right|-\left|\sqrt{3}+6\right|\)

\(=6-\sqrt{3}-\sqrt{3}-6\)

\(=-2\sqrt{3}\)

3 tháng 7 2015

\(\sqrt{31-12\sqrt{3}}+\sqrt{31+12\sqrt{3}}\)

=\(\sqrt{\left(3\sqrt{3}\right)^2-2.3\sqrt{3}.2+4}+\sqrt{\left(3\sqrt{3}\right)^2+2.3\sqrt{3}.2+4}\)

=\(\sqrt{\left(3\sqrt{3}-2\right)^2}+\sqrt{\left(3\sqrt{3}+2\right)^2}\)

=\(3\sqrt{3}-2+3\sqrt{3}+2=6\sqrt{3}\)

13 tháng 9 2021

a, \(\sqrt{17-12\sqrt{2}}-\sqrt{17+12\sqrt{2}}\)

\(=\sqrt{17-2.3.2\sqrt{2}}-\sqrt{17+2.3.2\sqrt{2}}\)

\(=\sqrt{9-2.3.2\sqrt{2}+8}-\sqrt{9+2.3.2\sqrt{2}+8}\)

\(=\sqrt{\left(3-2\sqrt{2}\right)^2}-\sqrt{\left(3+2\sqrt{2}\right)^2}=\left|3-2\sqrt{2}\right|-\left|3+2\sqrt{2}\right|\)

\(=3-2\sqrt{2}-3-2\sqrt{2}=-4\sqrt{2}\)

b, \(\sqrt{31-12\sqrt{3}}-\sqrt{31+12\sqrt{3}}\)

\(=\sqrt{31-2.2.3\sqrt{3}}-\sqrt{31+2.2.3\sqrt{3}}\)

\(=\sqrt{\left(3\sqrt{3}-2\right)^2}-\sqrt{\left(3\sqrt{3}+2\right)^2}=\left|3\sqrt{3}-2\right|-\left|3\sqrt{3}+2\right|\)

\(=3\sqrt{3}-2-3\sqrt{3}-2=-4\)

6 tháng 7 2018

a ) 

\(\sqrt{31}+4< \sqrt{36}+4=10\left(1\right)\)

\(6+\sqrt{17}>6+\sqrt{16}=6+4=10\left(2\right)\)

Từ ( 1 ) ; ( 2 ) 

\(\Rightarrow\sqrt{31}+4< 10< 6+\sqrt{17}\)

\(\Rightarrow\sqrt{31}+4< \sqrt{17}+6\)

b ) 

\(\sqrt{3}+\sqrt{2}>\sqrt{1}+\sqrt{1}=2\)

c ) 

\(\sqrt{12+13}=\sqrt{25}=5\left(1\right)\)

\(\sqrt{12}+\sqrt{13}>\sqrt{4}+\sqrt{9}=2+3=5\left(2\right)\)

Từ ( 1 ) ; ( 2 ) 

\(\Rightarrow\sqrt{12+13}< \sqrt{12}+\sqrt{13}\)

26 tháng 10 2018

:V

khó vc

26 tháng 6 2017

a. Ta co: \(2\sqrt{31}=\sqrt{2^2\cdot31}=\sqrt{124}\)

\(10=\sqrt{10}\)

\(Vi\sqrt{10}< \sqrt{124}hay10< 2\sqrt{31}\)

26 tháng 6 2017

c.. \(6+2\sqrt{2}=6+\sqrt{8}=\sqrt{6}+\sqrt{8}=\sqrt{14}\)(1)

\(9=\sqrt{3}\)(2)

Ta co (1)>(2) hay \(\sqrt{14}>\sqrt{3}\) nen \(6+2\sqrt{2}>9\)

24 tháng 6 2019

\(E=\)( ghi đề vào đây )

\(E=\sqrt[3]{4+\frac{5}{3}.\frac{\sqrt{31}}{\sqrt{3}}}+\sqrt[3]{4-\frac{5}{3}.\frac{\sqrt{31}}{3}}\)

\(E=\sqrt[3]{4+\frac{5\sqrt{31}}{3\sqrt{3}}}+\sqrt[3]{4+\frac{5.\sqrt{31}}{3\sqrt{3}}}\)

\(E\approx1\)

NV
24 tháng 6 2019

\(E^3=4+\frac{5}{3}\sqrt{\frac{31}{3}}+4-\frac{5}{3}\sqrt{\frac{31}{3}}+3\sqrt[3]{\left(16-\frac{25}{9}.\frac{31}{3}\right)}\left(\sqrt[3]{4+\frac{5}{3}\sqrt{\frac{31}{3}}}+\sqrt[3]{4-\frac{5}{3}\sqrt{\frac{31}{3}}}\right)\)

\(\Leftrightarrow E^3=8-7E\)

\(\Leftrightarrow E^3+7E-8=0\)

\(\Leftrightarrow\left(E-1\right)\left(E^2+E+8\right)=0\)

\(\Leftrightarrow E=1\)

Bài 3:

a) Ta có: \(4+2\sqrt{3}\)

\(=3+2\cdot\sqrt{3}\cdot1+1\)

\(=\left(\sqrt{3}+1\right)^2\)

b) Ta có: \(7+4\sqrt{3}\)

\(=4+2\cdot2\cdot\sqrt{3}+3\)

\(=\left(2+\sqrt{3}\right)^2\)

c) Ta có: \(9+4\sqrt{5}\)

\(=5+2\cdot\sqrt{5}\cdot2+4\)

\(=\left(\sqrt{5}+2\right)^2\)

d) Ta có: \(31+10\sqrt{6}\)

\(=25+2\cdot5\cdot\sqrt{6}+6\)

\(=\left(5+\sqrt{6}\right)^2\)

e) Ta có: \(13+4\sqrt{3}\)

\(=12+2\cdot2\sqrt{3}\cdot1+1\)

\(=\left(2\sqrt{3}+1\right)^2\)

g) Ta có: \(21+12\sqrt{3}\)

\(=12+2\cdot2\sqrt{3}\cdot3+9\)

\(=\left(2\sqrt{3}+3\right)^2\)

h) Ta có: \(29+12\sqrt{5}\)

\(=20+2\cdot2\sqrt{5}\cdot3+3\)

\(=\left(2\sqrt{5}+3\right)^2\)

i) Ta có: \(49+8\sqrt{3}\)

\(=48+2\cdot4\sqrt{3}\cdot1\)

\(=\left(4\sqrt{3}+1\right)^2\)

k) Sửa đề: \(14-6\sqrt{5}\)

Ta có: \(14-6\sqrt{5}\)

\(=9-2\cdot3\cdot\sqrt{5}+5\)

\(=\left(3-\sqrt{5}\right)^2\)

l) Ta có: \(23-8\sqrt{7}\)

\(=16-2\cdot4\cdot\sqrt{7}+7\)

\(=\left(4-\sqrt{7}\right)^2\)

m) Ta có: \(15-4\sqrt{11}\)

\(=11-2\cdot\sqrt{11}\cdot2+4\)

\(=\left(\sqrt{11}-2\right)^2\)

n) Sửa đề: \(28-10\sqrt{3}\)

Ta có: \(28-10\sqrt{3}\)

\(=25-2\cdot5\cdot\sqrt{3}+3\)

\(=\left(5-\sqrt{3}\right)^2\)

o) Ta có: \(17-12\sqrt{2}\)

\(=9-2\cdot3\cdot2\sqrt{2}+8\)

\(=\left(3-2\sqrt{2}\right)^2\)

p) Ta có: \(43-30\sqrt{2}\)

\(=25-2\cdot5\cdot3\sqrt{2}+18\)

\(=\left(5-3\sqrt{2}\right)^2\)

q) Ta có: \(51-10\sqrt{2}\)

\(=50-2\cdot5\sqrt{2}\cdot1\)

\(=\left(5\sqrt{2}-1\right)^2\)

r) Ta có: \(49-12\sqrt{5}\)

\(=45-2\cdot3\sqrt{5}\cdot2+4\)

\(=\left(3\sqrt{5}-2\right)^2\)

21 tháng 6 2018

\(1)\) Ta có : 

\(\left(\sqrt{3\sqrt{2}}\right)^4=\left[\left(\sqrt{3\sqrt{2}}\right)^2\right]^2=\left(3\sqrt{2}\right)^2=9.2=18\)

\(\left(\sqrt{2\sqrt{3}}\right)^4=\left[\left(\sqrt{2\sqrt{3}}\right)^2\right]^2=\left(2\sqrt{3}\right)^2=4.3=12\)

Vì \(18>12\) nên \(\left(\sqrt{3\sqrt{2}}\right)^4>\left(\sqrt{2\sqrt{3}}\right)^4\)

\(\Rightarrow\)\(\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)

Vậy \(\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)

Chúc bạn học tốt ~